Relegated cultural heritage in the Historic Center of Ayacucho. Provincial municipal management (2019-2022) - Mejia Curahua, Jhumera (2024)
The Historic Center of Ayacucho (CHA) has a rich cultural history; therefore, the management developed by the local government must guarantee its transcendence and dynamism. The objective of this work is to evaluate whether the institutional strategies used during the period 2019-2022 contributed to the development of the CHA. For this purpose, the methodology applied for the analysis of management mechanisms follows a qualitative approach applied to the sample of the CHA during the 2019-2022 management period. The results of the analysis of the management mechanisms evidenced an imbalance between what was proposed and what was executed during that management, one aspect that was taken into account was the COVID-19 pandemic that left on hold the possibility of international cooperation for the improvement of the CHA. From what was observed, we conclude that there is a need for larger projects to improve the objects and heritage values of the CHA.